Impact of Agglomerations on the Development of Surrounding Areas: Novosibirsk, Moscow and St. Petersburg Agglomerations - Pavel Vasilyevich Druzhinin; Marina Valeryevna Moroshkina; Ksenija Evgenievna Sedova (Prostranstvennaâ Èkonomika)
The article examines the development of regions and individual municipalities of the Siberian Federal District (SFD) in conditions of population concentration in the Novosibirsk agglomeration. The purpose of the research is to assess the impact of the concentration of population and other resources in the Novosibirsk agglomeration on the development of municipalities and regions of the Siberian Federal District in comparison with the Moscow and St. Petersburg agglomerations. To achieve this goal, the dynamics of the population of municipalities is analyzed and modeled depending on the distance to the center of the agglomeration, the aggregation of the regions of the Siberian Federal District is carried out and production functions are built for the resulting four groups of regions. It is shown that the dynamics of the population of municipalities near the Moscow, St. Petersburg and Novosibirsk agglomerations is described by similar equations, but the positive influence of Moscow extends further and the outflow of population to the Novosibirsk agglomeration is significantly less. The regions around the Leningrad and Novosibirsk regions are developing noticeably slower, their population is rapidly decreasing, the migration balance is negative and their efficiency is lower. In the regions closest to the Novosibirsk Region, the elasticity of funds is low, in the more distant ones it is significantly higher, and the elasticity of labor for both is more than one, but much less than in similar regions of the Central Federal District